Lercom e escrevercom o educador F. D.: delyneando circunstâncias - Rampon, Camille Luzia Grizon (My University, 2024)
The research falls within the line of inquiry of History and Philosophy of Education and is linked to the study group of Pedagogy of Difference. Cartography occurs through the lerCOM and escreverCOM method (SILVA et al., 2017) F.D. and the book The Effective Vagabonds, workers, artists, revolutionaries: educators (DELIGNY, 2018). ReadingCOM and writingCOM produce maps, forge encounters, and create montages throughout the research. The blocks that make up the text express the movements carried out through the specific objectives, which are: (I) Forging the encounter with some biographical elements of Deligny with the research theme. In this first movement and objective, the encounter with the research territory takes place, presenting the theme while simultaneously approaching the method and the research problem. (II) Delyneating Deligny's "attempts," marking the first Deligny attempt. Here, the delyneaments produced by Deligny's three "attempts" are marked, showing a reading that writes through the encounter with F.D. (III and IV) Reading and writing with the book The Effective Vagabonds, workers, artists, revolutionaries: educators (DELIGNY, 2018), the research extracts the trace of an educator. An educator is a facilitator of circumstances. The circumstances of life. Eternal writer, somewhat mocking those who look for formulas, Deligny leaves us clues. [resumo fornecido pelo autor]
A pesquisa insere-se na linha de pesquisa História e Filosofia da Educação e está vinculada ao grupo de estudos da Pedagogia da Diferença. A cartografia acontece pelo método lerCOM e escreverCOM (SILVA et al., 2017) F.D. e o livro Os Vagabundos Eficazes, operários, artistas, revolucionários: educadores (DELIGNY, 2018). A leituraCOM e a escritaCOM produzem mapas, forjam encontros e montagens ao longo da pesquisa. Os blocos que compõem o texto expressam os movimentos realizados por meio dos objetivos específicos, que são: (I) Forjando o encontro com alguns elementos biográficos de Deligny com a temática de pesquisa. Neste primeiro movimento e objetivo acontece o encontro com o território de pesquisa, apresentando a temática, ao mesmo tempo, em que se aproxima do método e do problema de pesquisa. (II) Delyneando as tentativas de Deligny, marcando a primeira tentativa-Deligny. Aqui, marcam-se os delyneamentos produzidos pelas três tentativas de Deligny, mostrando uma leitura que escreve pelo encontro com F.D. (III e IV) Lendo e escrevendo com o livro Os Vagabundos Eficazes, operários, artistas, revolucionários: educadores (DELIGNY, 2018), a pesquisa extrai o vestígio de um educador. Um educador é um possibilitador de circunstâncias. As circunstâncias da vida. Eterno escritor, meio que zombando daqueles que procuram por formulinhas, Deligny nos deixa pistas. [resumo fornecido pelo autor]
Keywords: Educadores; Leitura; Educação; Escrita; Educators; Reading; Education; Writing